FOREIGN LAW IN COMBATING ILLICIT DRUGS - A. E. Shalagin (Russian Journal of Economics and Law, 2011)
RETRACTION:Date: 02.05.2022Reason: Partial or full duplication of articles in the Actual Problems of Economics and Law Journal with previously published texts was detected. For example, an article was published in the Journal:SHALAGIN A. FOREIGN LAW IN COMBATING ILLICIT DRUGS // Actual Problems of Economics and Law. 2011. № 4. С. 291-295. (https://www.elibrary.ru/item.asp?id=17073726). The article contains large extracts from the previously published article:ШАЛАГИН А.Е., КАБИРОВ Д.Э. ОТВЕТСТВЕННОСТЬ ЗА НЕЗАКОННЫЙ ОБОРОТ НАРКОТИЧЕСКИХ СРЕДСТВ В ЗАРУБЕЖНОМ ЗАКОНОДАТЕЛЬСТВЕ // Вестник казанского юридического института МВД России. 2011. № 4. С. 291-295. (https://www.elibrary.ru/item.asp?id=17829332).Thr Editorial Board of the Journal, when publishing scientific research materials, bases its performance on the rules of publication ethics observed by the Editorial Board members, reviewers and authors. According to these rules, the author shall guarantee that the article is published for the first time and was not previously published or submitted to another journal. The Editorial Board performed an internal investigation. The Editor-in-Chief and the Publisher made a decision to retract the article from elibrary.ru and the Journal website.